Ответы и объяснения

2012-11-06T01:10:58+04:00

\lim_{x \to 1} \frac{\sqrt{2x+3}-\sqrt{4+x}}{3x^2-4x+1}

 

Умножим числитель на сопряженное и соответственно разделим

 

\lim_{x \to 1} \frac{\sqrt{2x+3}-\sqrt{4+x}}{3x^2-4x+1}*\frac{\sqrt{2x+3}+\sqrt{4+x}}{\sqrt{2x+3}+\sqrt{4+x}}=

=\lim_{x \to 1} \frac{(2x+3)-(4+x)}{(3x^2-4x+1)*(\sqrt{2x+3}+\sqrt{4+x})}=

=\lim_{x \to 1} \frac{(x-1)}{(3x^2-4x+1)*(\sqrt{2x+3}+\sqrt{4+x})}=

=\lim_{x \to 1} \frac{(x-1)}{(3x-1)(x-1)*(\sqrt{2x+3}+\sqrt{4+x})}=

\lim_{x \to 1} \frac{1}{(3x-1)*(\sqrt{2x+3}+\sqrt{4+x})}=\frac{1}{4\sqrt{5}}